A Constrained Analysis of the 40Ca(18O,18F)40K Direct Charge Exchange Reaction Mechanism at 275 MeV - Cavallaro, Manuela; Bellone, Jessica I.; Calabrese, Salvatore; Agodi, Clementina; Burrello, Stefano; Cappuzzello, Francesco; Carbone, Diana; Colonna, Maria; Deshmukh, N.; Lenske, H.; Spatafora, A.; Acosta, L.; et al. (Frontiers in Astronomy and Space Sciences, 2021)
The 40Ca(18O,18F)40K single charge exchange (SCE) reaction is explored at an incident energy of 275 MeV and analyzed consistently by collecting the elastic scattering and inelastic scattering data under the same experimental conditions. Full quantum-mechanical SCE calculations of the direct mechanism are performed by including microscopic nuclear structure inputs and adopting either a bare optical potential or a coupled channel equivalent polarization potential (CCEP) constrained by the elastic and inelastic data. The direct SCE mechanism describes the magnitude and shape of the angular distributions rather well, thus suggesting the suppression of sequential multi-nucleon transfer processes.